TREM2+ macrophages: a key role in disease development - Wang, Xinxin; Wang, Yunhan; Yang, Lei; Zhang, Yi; Yang, Li (Frontiers in Immunology, 2025)
Triggering receptors expressed on myeloid cells 2 (TREM2), an immune receptor expressed on myeloid cells, has garnered considerable attention in recent years due to its role in unique signaling pathways and diverse biological functions, including phagocytosis, lipid metabolism, cell survival, and inflammatory responses. Although TREM2 is expressed in various cell types, such as macrophages, dendritic cells (DCs), osteoclasts, and others, where it exhibits context-dependent functional characteristics, it is mainly expressed in macrophages. Notably, TREM2 is implicated in the development and progression of multiple diseases, playing dual and often opposing roles in noncancerous diseases and cancers. This review aims to highlight the pivotal role of TREM2 in macrophages and immune-related diseases, elucidate its underlying mechanisms of action, explore its potential as a clinical diagnostic and prognostic marker, and propose therapeutic strategies targeting TREM2 based on current clinical trial data, providing comprehensive guidance and references for clinical practice.